MEDIA PEMBELAJARAN TEKNOLOGI DIGITAL UNTUK MENINGKATAN EFEKTIVITAS BELAJAR SISWA PADA ABAD-21 - Estin Farida (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
Living in the 21st century, almost all activities cannot be detached from digital technology. Most elementary school children are actively using digital technology, including the 5th graders of SD Muhammadiyah Sapen who 88% own smartphones. They use them for social media and entertainment. They are more interested in playing smartphones than studying. They also think the learning materials in the fifth grade are difficult. Even, some children’s learning outcomes are low in the fifth grade. If this situation is permitted, their learning effectiveness will be lowered. Therefore, this best practice is intended to improve the children’s learning effectiveness in fifth grade. The teacher must be able to create appropriate and millennial learning media for them or to become a Youtuber teacher. A Youtuber teacher is a teacher who is able to create and upload learning videos on YouTube. Video creation used laptops and smartphones equipped with PowerPoint applications, factory formats, and viva video. Afterward, the videos are uploaded to the Estin Farida Channel through Youtube. Video links are shared via social media and interactive books or modules. The creation of learning videos uploaded through youtube could improve the children’s learning effectiveness in SD Muhammadiyah Sapen. This can be noticed from the improvements of the learning quality, motivation, learning activities, readiness to receive the lessons, space and time flexibility to stud, and their learning outcomes. Another effect is creativity enhancement and digital literacy. In addition, the videos uploaded on Youtube could be used by almost everyone in SD Muhammadiyah Sapen.